2019
DOI: 10.15406/joentr.2019.11.00426
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery in hemangiomas of paranasal sinuses and nasal cavity

Abstract: Objectives: To determine the possibility of performing complete resections of rhinosinusal hemangiomas greater than 2cm treated by an endonasal approach assisted with endoscopes. Study design: Descriptive, retrospective Methods: We analyzed the clinical histories of all adult patients who underwent an endonasal approach with endoscopes, for having hemangiomas of the nasal cavity and paranasal sinuses in the Italian Hospital of Buenos Aires, between June 2006 and December 2016. We excluded patients with heman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The combination of estrogen and progesterone would increase venous distensibility, and stimulate endothelial proliferation, although no receptors for these hormones have been detected in 21 lobulated capillary hemangiomas. [7][8][9][10] In another study, 2 recurrences were reported in 37 patients treated with endonasal surgery with endoscopes. 3 In all the studies referred to above, they used local anesthesia to operate patients with smaller hemangiomas, which originated in the nasal cavity and in which they identified the implantation site.…”
Section: Individual Treatment Is Based On Tumor Size Age and Patientmentioning
confidence: 99%
“…The combination of estrogen and progesterone would increase venous distensibility, and stimulate endothelial proliferation, although no receptors for these hormones have been detected in 21 lobulated capillary hemangiomas. [7][8][9][10] In another study, 2 recurrences were reported in 37 patients treated with endonasal surgery with endoscopes. 3 In all the studies referred to above, they used local anesthesia to operate patients with smaller hemangiomas, which originated in the nasal cavity and in which they identified the implantation site.…”
Section: Individual Treatment Is Based On Tumor Size Age and Patientmentioning
confidence: 99%